Constructing scientific communities: citizen science in the Nineteenth and Twenty-First Centuries - Shuttleworth, S; Dawson, G; Lintott, C (Taylor and Francis (Routledge), 2015)
‘I like all scientific periodicals’, Charles Darwin told Joseph Hooker in November 1869. His fondness for such publications seemed to have no bounds, and, unlike more snooty contemporaries like Hooker, he avidly read even those journals he considered ‘rather ephemeral’, including such self-consciously demotic titles as the Popular Science Review and Scientific Opinion. A particular favourite of Darwin’s was the Magazine of Natural History, which he called ‘Loudon’s and Charlesworth’s Journal’ after its initial two editors, John Claudius Loudon and his successor Edward Charlesworth. What Darwin admired about the Magazine of Natural History under their respective editorships, which together lasted from the 1820s to the 1840s, was its willingness to publish ‘discussions and observations on what the world would call trifling points in Natural History’. Many of these seemingly ‘trifling points’ were contributed by men and (more occasionally) women who operated far from the genteel drawing rooms of the scientific elite, whether as commercial traders in smelly commodities like bird skins or lowly artisans who spent their limited leisure time observing local flora and fauna. Such quotidian contributions, as Darwin noted, would never be permitted in ‘foreign periodicals’, prompting him to reflect: ‘and a great loss it has always appeared to me’. Darwin’s regret at the haughtiness of such Continental journals as the Annales du Muséum National d’Histoire Naturelle was genuine, as their more egalitarian British counterparts afforded him a vital source of descriptive information and detailed data in the period when he was initially formulating the theory of natural selection. It was, as any reader of On the Origin of Species (1859) will immediately recognize, through the accumulation of precisely such small facts and observations that Darwin was able to forge the momentous theoretical generalizations that would have such a profound impact on his contemporaries and the modern world.